2021
DOI: 10.1002/rmv.2276
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine in the treatment of coronavirus disease 2019: Rapid updated systematic review and meta‐analysis

Abstract: Summary Coronavirus disease 2019 (COVID‐19) caused by the novel severe acute respiratory syndrome coronavirus 2 continues to grow and spread throughout the world since being declared a pandemic. Despite extensive scientific research globally including repurposing of several existing drugs, there is no effective or proven therapy for this enigmatic disease which is still largely managed empirically This systematic review evaluated the role of hydroxychloroquine (HCQ) in the treatment of COVID‐19 infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Hydroxychloroquine (HCQ), belongs to the 4­aminoquinolines class with antimalarial activity and an immunomodulatory effect (Schrezenmeier and Dörner 2020 ; Munguía-Realpozo et al, 2021 ; Gupta et al 2022 ). It has also been used clinically in the treatment of systemic lupus erythematosus (SLE) (Costedoat-Chalumeau et al 2014 ; Broder et al 2021 ), downregulating pro-inflammatory cytokines and immunoglobulin, eliminating autoreactive lymphocytes, ultimately improves patient survival and relieves severe lupus symptoms (Takamasu et al 2019 ; Ponticelli and Moroni 2017 ; Willis et al 2012 ; Rainsford et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine (HCQ), belongs to the 4­aminoquinolines class with antimalarial activity and an immunomodulatory effect (Schrezenmeier and Dörner 2020 ; Munguía-Realpozo et al, 2021 ; Gupta et al 2022 ). It has also been used clinically in the treatment of systemic lupus erythematosus (SLE) (Costedoat-Chalumeau et al 2014 ; Broder et al 2021 ), downregulating pro-inflammatory cytokines and immunoglobulin, eliminating autoreactive lymphocytes, ultimately improves patient survival and relieves severe lupus symptoms (Takamasu et al 2019 ; Ponticelli and Moroni 2017 ; Willis et al 2012 ; Rainsford et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, while differences were observed in the administration of hydroxychloroquine or corticosteroids among those with baseline high or low NT-proBNP values, subsequent studies have revealed that the use of hydroxychloroquine in the acute phase does not reduce mortality [ 33 34 ], nor do corticosteroids benefit non-severe patients [ 33 , 35 ]. As a result, their widespread use is no longer recommended.…”
Section: Discussionmentioning
confidence: 87%
“… 68 Previous meta-analysis has proved that although HCQ treatment is safe, it could not decrease mortality or promote clinical/virological recovery in COVID-19 patients. 69 Whereas the evidence supporting the HCQ treatment for COVID-19 is not clear, HCQ has shown great efficacy against immune-mediated diseases. Therefore, physicians and individuals should avoid misuse of HCQ for the prophylaxis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%